2019
DOI: 10.1111/jfpp.14094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the chemical refining process on perilla seed oil composition and oxidative stability

Abstract: The effect of chemical refining process on the physicochemical characteristics and oxidative stability of perilla seed oil was investigated. We analyzed five samples corresponding to each step of the refining process (degumming, neutralization, bleaching, deodorization, and refined oil). The results indicated that the acid value (2.20–0.24 mg KOH/g) and peroxide value (4.32–1.26 mEq/kg) decreased significantly, while the saponification value (178.81–196.24 mg KOH/g) and p‐anisidine value (3.45–9.55) increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
(78 reference statements)
2
12
0
Order By: Relevance
“…It has been reported that the tocopherol content of polyunsaturated fatty acid (PUFA) rich oils was higher than that of the oleic acid-rich oils 22) . With good antioxidant, tocopherol in the perilla oil could reduce free radical, therefore protecting the unsaturated fatty acids of the oil 1) . However, the unsaponifiable matter of this oil was only 0.57 g/100 g, relatively lower than oliver oil (1.23 g/100 g) , peanut oil (0.94 g/100 g) and sunflower oil (0.81 g/100 g) 23) .…”
Section: Physicochemical Parameters Of Perilla Seed Oilmentioning
confidence: 99%
“…It has been reported that the tocopherol content of polyunsaturated fatty acid (PUFA) rich oils was higher than that of the oleic acid-rich oils 22) . With good antioxidant, tocopherol in the perilla oil could reduce free radical, therefore protecting the unsaturated fatty acids of the oil 1) . However, the unsaponifiable matter of this oil was only 0.57 g/100 g, relatively lower than oliver oil (1.23 g/100 g) , peanut oil (0.94 g/100 g) and sunflower oil (0.81 g/100 g) 23) .…”
Section: Physicochemical Parameters Of Perilla Seed Oilmentioning
confidence: 99%
“…Based on Table 2, both WD and AD were insignificantly different (p > 0.05) from each other in affecting the PV (3.33 ± 0.01 meq/kg), and these two methods significantly decreased the PV of the oil samples as compared to that of crude MO kernel oil (p < 0.05). A significant decrease in PV upon degumming was also reported in the case of MO kernel oil from seeds of South Sonora (Mexico) origin [9], kenaf seed oil [12], and perilla seed oil [21]. Decrease in the PV consequently resulted in degummed (WD and AD) oil samples with significantly lower total oxidation (TOTOX) values, with oil sample subjected to AD showing significantly lower value as compared to that which is subjected to WD.…”
Section: Resultsmentioning
confidence: 59%
“…In contrast, Sánchez-Machado et al [9] reported that neutralization did not significantly affect the PV of MO kernel oil, yet increased the oil's p-AV. Neutralization also significantly decreased the PV of perilla [21] and kenaf [12] seed oils, and increased the p-AV of these oils. On the other hand, both Yoon [25] and Lee et al [21] reported a significant increase (p < 0.05) in the PV of neutralized chufa oil and camellia seed oil, respectively.…”
Section: Neutralizationmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous studies, optimization of refining conditions to reduce the formation of toxic contaminants such as 3-MCPD and GE in palm oil and olive oil has been studied (Özdikicierler et al, 2016;Zulkurnain et al, 2013). Since the elevated temperatures applied at deodorization cause a decrease in bioactive compounds such as tocopherols, sterols and phenolic compounds, optimization of the refining conditions to reduce the detrimental effect of refining has been discussed in several studies (Ceriani et al, 2008;Liu et al, 2019;Marangoni et al, 2019;Pan et al, 2019;Xie et al, 2019). Trans isomerization occurred during deodorization is another important issue investigated in many studies (Ceriani and Meirelles, 2007;Hénon et al, 1999;Kemény et al, 2001).…”
Section: Introductionmentioning
confidence: 99%